A case‐crossover study of age group differences in objective working‐hour characteristics and short sickness absence. (20th April 2020) - Ropponen, Annina; Koskinen, Aki; Puttonen, Sampsa; Härmä, Mikko
Abstract: Aim: To investigate age group differences in objective working‐hour characteristics and their associations with short (1–3 days) sickness absence. Background: Irregular working hours, that is shift work with non‐standard schedule, may influence sickness absence rates in hospital workers. Methods: We collected daily working hours and the first incidence of short sickness absence from the employers' electronic records from 2008 to 2017. A case‐crossover study compared the characteristics of the working hours 28 days preceding the sickness absence (exposure window) and 28 days earlier (control window) across 10‐year age groups (conditional logistic regression for odds ratios (OR) with 95% confidence intervals (95% CI)). Results: Younger employees had longer working hours and more night and consecutive shifts. Extended weekly working hours were associated with short sickness absence in all age groups. Age‐related differences were few: extended working hours among oldest age group (OR: 1.01, 95% CI: 1.00–1.01) and daily working hours in the youngest and middle‐age groups (Ors: 1.14–1.17) were associated with increased sickness absence. Conclusions: Length of working hours, and night and consecutive shifts differed between age, but the associations with short sickness absence were similar across all age groups. Implications for Nursing Management: Among older employees, the length of working hours should be paid special attention.